Differentiated Instruction in Merdeka Belajar Curriculum: Teachers’ Perception in EFL Context - Notanubun, Fitri Faradila; Lekatompessy, Jeny; Camerling, Bella (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2025)
This study investigates English teachers' perceptions, challenges, and how they overcome implementing Differentiated Instruction within the Merdeka Curriculum in the EFL context. The researcher used a narrative inquiry approach, including Document, Observation class, and Interview. This research describes and explains the experiences of 2 English Teachers in applying DI to support the Merdeka Belajar curriculum. Participants were purposively selected from SMA Negeri 2 Ambon, specifically those involved in the Guru Penggerak program batch 1 in 2020. The findings reveal that teachers perceive DI as a practical approach to addressing diverse student needs and enhancing engagement and achievement. They demonstrate a strong understanding of DI principles, tailoring content, processes, and products to individual students. Despite encountering significant internal challenges such as self-efficacy and external challenges like time management and resource allocation, teachers employ strategies including collaboration with colleagues, thorough preparation, effective group management, and fostering open communication. These efforts help manage the complexities of DI, ensuring a responsive and inclusive learning environment.